The Role of Transformational Leadership in Improving Employee Performance at the NTB Provincial Cultural Park - Cahyani, Ni Putu Andhinnia Prita; Sudarma, I Made; Chandra, Edy (Universitas Pamulang, 2025)
This study analyzes how transformational leadership improves employee performance at the Cultural Park of West Nusa Tenggara Province. As a regional cultural preservation institution, the Cultural Park faces complex operational demands requiring adaptive human resource management. Using a qualitative phenomenological approach, this research explores employee experiences with transformational leadership implementation through in-depth interviews with 10 employees of varying tenure, participatory observation, and documentation analysis. Thematic analysis was applied focusing on Bass and Riggio's four dimensions of transformational leadership.Findings reveal that all four dimensions are effectively implemented. Leaders demonstrate idealized influence through caring behavior that serves as a role model. Inspirational motivation manifests in consistent vision communication and efforts to secure work facilities. Intellectual stimulation appears through openness to innovative ideas, particularly regarding digital adaptation. Individualized consideration is realized via personal attention and recognition aligned with employee characteristics. These practices significantly enhance performance by creating a conducive work environment and strengthening motivation.The study enriches transformational leadership theory in public sector cultural organizations and offers practical guidance for developing leadership quality in similar institutions, emphasizing the importance of supporting systems including adequate staffing, welfare improvement, and continuous capacity development for sustainable organizational performance.